KEEFEKTIFAN MEDIA PEMBELAJARAN BERBASIS WEB EDUCAPLAY TERHADAP HASIL BELAJAR SISWA KELAS 4 PADA MATERI HUBUNGAN SUMBER DAYA ALAM DENGAN LINGKUNGAN - Prisella Ula Asfida Alma; Dhian Dwi Nur Wenda; Nara Setya Wiratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science learning in fourth-grade students at Jegreg Elementary School does not yet utilize technology-based media, resulting in low student learning outcomes on the relationship between natural resources and the environment. Based on observations and interviews, only 10 of 30 students achieved the minimum grade point average (KKTP) (75). This study aims to determine the effectiveness of the web-based learning media educaplay on fourth-grade students' learning outcomes on the relationship between natural resources and the environment. This study used the Research and Development (R&D) method with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects were 30 fourth-grade students, with data collected through observation, interviews, and learning outcome tests. The learning media was tested on both a limited and a broad scale. The results of the limited scale trial showed a completion rate of 100%, and the broad scale trial showed a completion rate of 100%. These results indicate that the educaplay web-based learning media for the learning outcomes of grade 4 students on the material on the relationship between natural resources and the environment is very effective in improving student learning outcomes, exceeding the KKTP score, and can be used without the need for improvement.